Subscapularis Tendon Tears – Usefulness of Written MRI Reports for Guiding Patient Referral to Shoulder Specialists - Lenz, Robert; Kircher, Jörn; Schwalba, Knut; Weber, Marc-André; Tischer, Thomas (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2021)
Introduction Rotator cuff tears are one of the most common reasons for shoulder pain, and patients often present initially to general practitioners. However, subscapularis tears are especially difficult to diagnose and hence adequate therapy is often delayed. General practitioners or non-specialist orthopedic surgeons need reliable MRI findings to allow timely referral of patients to shoulder specialists. The purpose of this study was to determine the validity of the written MRI report of patients with arthroscopically proven subscapularis tendon tears.Method In this retrospective study, 97 patients (mean age 62.4 ± 10 years, 63 men) who underwent arthroscopic subscapularis repair between April 2013 and January 2015 by two experienced shoulder surgeons and who underwent a preoperative 1.5 T MRI study were included. All of these patients had high-field strength (i. e., ≥ 1.5 T) standard MRI scans performed within 4–164 (mean 57.4 ± 38.4) days before their arthroscopic procedures.Results and Conclusion Subscapularis tendon tears, verified by arthroscopy, were correctly identified in only 37 of 97 cases in the written report of the preoperative MRI. This resulted in an overall low sensitivity of 38.1 %. Correctly predicted lesions were as follows: Fox and Romeo I 29.4 % (5/17 patients), Fox and Romeo II 20 % (7/35 patients), Fox and Romeo III 46.7 % (14/30 patients) and Fox and Romeo IV 73.3 % (11/15 patients). In contrast, concurrent supraspinatus tendon tears were identified correctly in 88.2 % of patients (60/68 cases, sensitivity 88.2 %, specificity 96.5 %). Preoperative written radiology reports provided by a heterogeneous group of 39 presumably non-MSK-specialized radiologic centers do not reliably detect subscapularis tendon tears and are not sufficient for guiding patients to specialist centers. Compared to other rotator cuff injuries, this study shows difficulties in the correct diagnosis of subscapular tendon injuries. However, this is necessary to provide patients with timely therapy. It can be assumed that MRI review by musculoskeletal-specialized radiologists would more often than not lead to the correct diagnosis.Key Points: Citation Format
Keywords: subscapularis tear; MRI; sensitivity; healthcare research